Bioequivalence evaluation of two amlodipine salts, besylate and orotate, each in a fixed-dose combination with olmesartan in healthy subjects - Lee SY; Kim JR; Jung JA; Huh W; Bahng MY; Ko JW (Dove Medical Press, 2015)
Soo-Yun Lee,1 Jung-Ryul Kim,2,3 Jin Ah Jung,4 Wooseong Huh,2,5 Mi Young Bahng,6 Jae-Wook Ko1,2 1Department of Health Sciences and Technology, SAIHST, Sungkyunkwan University, Seoul, Republic of Korea; 2Department of Clinical Pharmacology and Therapeutics, Samsung Medical Center, Seoul, Republic of Korea; 3Department of Clinical Research Design and Evaluation, SAIHST, Sungkyunkwan University, Seoul, Republic of Korea; 4Department of Clinical Pharmacology, Inje University, Busan Paik Hospital, Busan, Republic of Korea; 5Department of Internal Medicine, Samsung Medical Center, Sungkyunkwan University School of Medicine, Seoul, Republic of Korea; 6Dong-A ST Co., Ltd., Seoul, Republic of Korea Abstract: A fixed-dose combination of amlodipine and olmesartan is used to treat high blood pressure in patients whose hypertension is not sufficiently controlled with either drug alone. The objective of this study was to evaluate the bioequivalence of two fixed-dose combinations, ie, amlodipine orotate/olmesartan medoxomil 10/40 mg and amlodipine besylate/olmesartan medoxomil 10/40 mg, in healthy subjects. A randomized, open-label, single-dose, two-sequence, two-period, crossover study was conducted in 30 healthy adult volunteers. Blood samples were collected for up to 72 hours post-dose in each period. Safety data included the results of physical examinations, clinical laboratory tests, vital signs, an electrocardiogram, and adverse events. For both amlodipine and olmesartan, the 90% confidence intervals for the geometric mean ratios of AUClast and time to peak plasma concentration fell within the bioequivalence acceptance criteria. The two fixed-dose combinations showed similar safety profiles. Amlodipine orotate/olmesartan medoxomil 10/40 mg was bioequivalent to amlodipine besylate/olmesartan medoxomil 10/40 mg. Keywords: amlodipine orotate, amlodipine besylate, olmesartan medoxomil, fixed-dose combination, bioequivalence